Postmodernism, Postmodern marketing, and the consumption behaviours of Millennials and Generation Z in South Africa - Mkhonto, Zonke Mbali (University of the Witwatersrand, Johannesburg, 2023)
There is an insufficient degree of research-related exploration and analysis in the postmodern marketing field or sphere in the context of consumer behaviours of the Generation Y (Millennials) and Generation Z in South Africa. Accordingly, this study explores the integration of and its application to postmodern marketing strategies, and also analyses the influences of these strategies on the consumption habits and behaviours of the Generation Y and Generation Z youth cohorts. In its focus on contributin towards the resolution of these research-related gaps, the study explored and analysed the application of postmodernism in respect of the principles or constructs of hyperreality, fragmentation, and reversals of production and consumption. These principles were then examined and integrated with postmodern marketing approaches such as the gamification, omnichannel, user-generated content, and experiential marketing strategies for broader understanding of the nature and impact of the identified consumption behaviours of the Millennials and Generation Z in South Africa. The methodology entailed a quantitative methodological approach since it is objective, systematic, more efficient and further amenable to testing of hypotheses. A self- administered online questionnaire designed by the researcher was utilised for data collection and as reference framework for statistical data analysis. The findings supported all the developed hypotheses, and further revealed, amongst others, that a positive and significant relationship between all constructs concerning the nature and impact of the identified consumption behaviours of the Millennials and Generation Z in South Africa. Notwithstanding these findings, the study supports and recommends further research (future studies) in the adoption and application of the omnichannel marketing strategy, which seemed to display the most dynamism in the context of correlation analysis and path modelling more than the other postmodern marketing constructs
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Hyperreality; fragmentation; reversal of production and consumption; gamification strategy; omnichannel strategy; user-generated content; experiential marketing; Generation Y; Generation Z; SDG-12: Responsible consumption and production